Crystallization and X‐ray structure determination of a thermoalkalophilic lipase from Geobacillus SBS‐4S. Issue 4 (2nd April 2013) - Tayyab, Muhammad; Rashid, Naeem; Angkawidjaja, Clement; Kanaya, Shigenori; Akhtar, Muhammad
<x xml:space="preserve">Abstract</x> A thermoalkalophilic lipase (LIPSBS) from the newly isolated Geobacillus strain SBS‐4S which hydrolyzes a wide range of fatty acids has been characterized. In the present study, the crystallization of purified LIPSBS using the sitting‐drop vapour‐diffusion method and its X‐ray diffraction studies are described. The crystals belonged to the orthorhombic space group P212121, with unit‐cell parameters a = 55.13, b = 71.75, c = 126.26 Å. The structure was determined at 1.6 Å resolution by the molecular‐replacement method using the lipase from G. stearothermophilus L1 as a model.